THE ANALYSIS OF SATISFACTION OF STUDENTS IN THE CHRISTIAN UNIVERSITY OF INDONESIA TOWARD ACADEMIC INFORMATION SYSTEM (AIS) SERVICE: (Case Study Of Students In The Christian University Of Indonesia) - Hutajulu, Oktafia Agrethia; Tobing, Fenny BNL (Universitas Kristen Indonesia, 2019)
In the research analysis of satisfaction of students in the christian university of indonesia toward academic information system (ais) service, using a research model that is